Formalization of an inner change (Journal of Parents and Teachers, 1995)
The importance of respect and dignity in education, as well as the need to establish rules to encourage discipline and participation. The educator's attitude and the physical structure of the classroom are fundamental to creating a safe and organized environment. Reflection on continuous improvement in teaching practice is invited.
Keywords: respect; dignity; discipline; continuous improvement